Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper analyzes budgetary developments in Ireland during the 1990s. The paper highlights that Irish fiscal policy has been central to the social consensus on macroeconomic policies. The economic buoyancy has reinforced this cycle by facilitating the tax cuts and increases in social spending that have been instrumental to the social consensus on policies, while also helping to keep deficits low. The paper also discusses the participation of Ireland in the European Monetary Union.